Gold nanoparticles for sustained antileukemia drug release: Development, optimization and evaluation by quality-by-design approach - Adena S.K.R.; Upadhyay M.; Vardhan H.; Mishra B. (My University, 2025)
Aim: To design, develop, optimize and evaluate sustained-release dasatinib-loaded gold nanoparticles (DSB-GNPs) to treat chronic myeloid leukemia (CML) by using quality by design. Materials & methods: In this study, we performed risk assessment, optimization, in vitro characterizations, stability study, drug release studies, cytotoxicity study and in vivo pharmacokinetic evaluation. Results: DSB-GNPs of desired size, entrapment, smooth, spherical, stable and sustained drug release for 48 h were achieved. DSB-GNPs exhibited significantly more percentage growth inhibition and enhanced systemic bioavailability compared with pure DSB. Conclusion: The in vitro and in vivo evaluation exhibited that the DSB-GNPs have a potential cytotoxic effect, systemic bioavailability and sustained release making them a promising system of DSB delivery in the treatment of chronic myeloid leukemia. © 2019 Future Medicine Ltd.